Comparative metabolomic responses of low- and high-cadmium accumulating genotypes reveal the cadmium adaptive mechanism in Brassica napus. (July 2020) - Mwamba, T.M.; Islam, F.; Ali, B.; Lwalaba, J.L.W.; Gill, R.A.; Zhang, F.; Farooq, M.A.; Ali, S.; Ulhassan, Z.; Huang, Q.; Zhou, W.; Wang, J.
Abstract: Recently, oilseed rape has gathered interest for its ability to withstand elevated metal contents in plant, a key feature for remediation of contaminated soils. In this study, comparative and functional metabolomic analyses using liquid chromatography/mass spectrometry were undertaken to explore the metabolic basis of this attribute under cadmium (Cd) stress. Results revealed both conserved and differential metabolomic responses between genotype CB671 (tolerant Cd-accumulating) and its sensitive counterpart ZD622. CB671 responded to Cd stress by rearranging carbon flux towards production of compatible solutes, sugar storage forms and ascorbate, as well as jasmonates, ethylene and vitamin B6. Intriguingly, IAA abundance was reduced by 1.91-fold, which was in connection with tryptophan funnelling into serotonin (3.48-fold rise). In ZD622 by contrast, Cd provoked drastic depletion of carbohydrates and vitamins, but subtle hormones alteration. A striking accumulation of unsaturated fatty acids and oxylipins in CB671, paralleled by glycerophospholipids build-up and induction of inositol-derived signalling metabolites (up to 5.41-fold) suggested ability for prompt triggering of detoxifying mechanisms. Concomitantly, phytosteroids, monoterpenes and carotenoids were induced, denoting fine-tuned mechanisms for membrane maintenance, which was not evident in ZD622. Further, ZD622 markedly accumulated phenolics from upstream sub-classes of flavonoids; in CB671 however, a distinct phenolic wiring was activated, prioritizing anthocyanins and lignans instead. Along with cell wall (CW) saccharides, the activation of lignans evoked CW priming in CB671. Current results have demonstrated existence of notable metabolomic-based strategies for Cd tolerance in metal-accumulating oilseed rapes, and provided a holistic view of metabolites potentially contributing to Cd tolerance in this species. Graphical abstract: Image 1 Highlights: Conserved and differential metabolic signatures were revealed in studied genotypes. Lipidic metabolites were key players for Cd tolerance in CB671 (Cd-accumulating). Positive shifts in CB671 mainly concerned signaling system and membranes integrity. Unlike ZD622, CB671 preferentially funelled flavonoids into anthocyanins. Concomitant induction of lignans and CW saccharides evoked CW priming in CB671.